CURRENT CONDITION OF THE RETAIL MARKET - Chernysheva N.M.; Kotov R.M.; Altynbaeva E.S.; Khristoforova Y.A. (Техника и технология пищевых производств)
Modern economic notions make the market participants introduce new competitive technologies of business management as well as consider and analyze more and more factors influencing success of business management. Fast moving consumer goods market is one of the the most dynamically developing segments of the market. It demonstrates high competition level and opposition and generates research interest. JSC «Tander» was chosen as a subject of the research. Russian and foreign economists’ works considering trading company competitive ability formed the theoretical basis of the research. The authors used analysis, synthesis, grouping and generalization of scientific data as the basic methods. The research has shown that network retail occupies the first place in the structure of retail trade format. Besides, there is an upward trend in the share of goods sold by means of promotional activities. There is a change in sales structure towards the decrease in the premium segment share and increase in an economy segment share. The share of sales in discounters is growing. Also there is a decrease in fresh products share in Russian people’s consumer goods basket. As Russian people prefer to cook at home more and more often there is a significant growth in sales of various ingredients for dishes and pastries cooking. As food is the last thing the consumers save money on this makes FMCG market (goods of daily consumption) the steadiest one even during economic downturn.